1999
DOI: 10.3109/08923979909007135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Withania Somnifera On Cytokine Production in Nol and Cyclophosphamide Treated Mice

Abstract: Administration of an extract from the powdered root of the plant Withania somnifera (Family: Solanaceae) enhanced the levels of Interferon gamma (IFN-gamma) (75.87 pg/ml), Interleukin-2 (IL-2) (14.16 pg/ml) and Granulocyte macrophage colony stimulating factor (GM-CSF) (49.22 pg/ml) in normal Balb/c mice. The lowered levels of IFN gamma--(30 pg/ml), IL-2 (4.5 pg/ml) and GM-CSF (19.12 pg/ml) after treatment with cyclophosphamide (CTX) was reversed by the administration of Withania somnifera extract (IFN gamma--7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Enhanced levels of interferon (IFN)-gamma, IL-2, and granulocyte macrophage colony-stimulating factor (GM-CSF) in normal BALB/c mice were observed on administration of extract from roots of Withania somnifera. The lowered levels of IFNgamma, IL-2, and GM-CSF after treatment with CP was reversed by administration of Withania somnifera extract with lowered levels of TNF-alpha, indicating immunopotentiating and myeloprotective effect (Davis and Kuttan, 1999). All these studies indicate various pharmacodynamic possibilities but based on previous studies indicate cytokine-mediated regulation by both, Withania and Tinospora leading to specific (cellular and antibody mediated) and non-specific (mainly macrophage mediated) immunoenhancement.…”
Section: Resultsmentioning
confidence: 78%
“…Enhanced levels of interferon (IFN)-gamma, IL-2, and granulocyte macrophage colony-stimulating factor (GM-CSF) in normal BALB/c mice were observed on administration of extract from roots of Withania somnifera. The lowered levels of IFNgamma, IL-2, and GM-CSF after treatment with CP was reversed by administration of Withania somnifera extract with lowered levels of TNF-alpha, indicating immunopotentiating and myeloprotective effect (Davis and Kuttan, 1999). All these studies indicate various pharmacodynamic possibilities but based on previous studies indicate cytokine-mediated regulation by both, Withania and Tinospora leading to specific (cellular and antibody mediated) and non-specific (mainly macrophage mediated) immunoenhancement.…”
Section: Resultsmentioning
confidence: 78%
“…(Ziauddin et al, 1996;Davis and Kuttan, 2000). More studies on lymphocytes subpopulations and Th cytokines are needed to better understand its immunological basis (Dhuley, 1997;Davis and Kuttan, 1999). Comparative studies with established immunomodulators were also needed and the present study is such an attempt.…”
Section: Discussionmentioning
confidence: 86%
“…Its biologically active constituents are alkaloids (isopelletierine, anaferine), steroidal lactones (withanolides, withaferins), saponins International Immunopharmacology 6 (2006) 1535 -1542 www.elsevier.com/locate/intimp containing an additional acyl group (sitoindoside VII and VIII), and withanolides with a glucose at carbon 27 [5]. Studies have demonstrated its anti-inflammatory [6], anti-tumor [7][8][9], anti-stress [10], anti-oxidant [11][12][13], anti-aging [14,15], analgesic [16] and hemato/ immunomodulator activities [17][18][19][20][21]. The use of W. somnifera has been mainly associated to its modulatory effect on the immune system [22].…”
Section: Introductionmentioning
confidence: 99%